Os efeitos e as medidas: crise e contrarreformas e as respostas da FEM-CUT/SP - Pereira, Eduardo José Rezende (Universidade Federal de São Carlos, 2019)
The international crisis of the capitalist system affects the economic development indices of central and peripheral countries. Brazil feels the deepening effects of this economic crisis along with a political crisis, which places employers' interests on the government's agenda. Deindustrialization and the retrogression of social and labor legislation cause difficulties in the form of collective organization of the working class. We seek to understand how the Federation of Metalworkers Unions of the Central Única de Trabalhadores de São Paulo (FEM-CUT/SP) operates in this scenario, mapping its responses and classifying them in two ways: those related to organizational and financial changes of the entity, and also those related to readjustments of tactics and political discourse.
The effects and the measures: crisis and counter-reforms and the responses of FEM-CUT/SP
Keywords: Sindicalismo; Crise; Retrocessos sociais.; Reforma trabalhista; Unionism; Crisis; Labor reform; Social setbacks; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS